PEDAGOGICAL CONDITIONS OF IMPROVEMENT OF SOCIAL PEDAGOGICAL ACTIVITY OF STUDENTS ON THE BASIS OF MULTIMEDIA TOOLS - Rahimova Feruza Najmiddinovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the principles of the organization of creative and creative activities of students on the basis of social pedagogical activity and multimedia in higher educational institutions and integration in the socio-pedagogical process are expressed.